“Desarrollo de los módulos de gestión de proyectos y grupos de investigación en la plataforma Ecuciencia” - Jaramillo Tenezaca, Ginger Lissbeth (2021)
This work is part of the research project "Scientometric Studies Network (REDEC)", the same one that belongs to the Technical University of Cotopaxi, whose objective is to manage the information of research groups and projects that the institution has. The Computer Science and Computer Systems Engineering career contributes to this project through the development and deployment of modules for project management and research groups on the EcuCiencia platform, the work has been adjusted to the needs raised by the project coordinator , in such a way that it allows the entry of the information of the research groups and projects, visualization of the graph of scientific production by project and the downloading of the information of the registered groups. Free software tools were used to develop the modules: Django, Python, PostgreSQL; In addition, the Iterative Incremental model was applied, which allowed, through the execution of its different phases, to obtain a first test product to later refine the functionalities until reaching the final implementation of the modules. The modules developed are in production, working with real data, which allows determining the fulfillment of the objectives proposed for this part of the work; later, new functionalities will be implemented depending on the future requirements of the EcuCiencia platform.